Effectiveness of direct corrective feedback in use of articles among Iranian EFL medical students and their attitudes towards the feedback - Soori, Afshin (2012)
The current study investigated whether different types of direct corrective feedback are effective in the correct use of English articles and to compare the effectiveness of these types of corrective feedback. In addition, the study tried to determine the sustained effects of the different types of direct corrective feedback on the use of English articles. The relationship between the students’ attitudes towards the different types of corrective feedback they received during the treatment and the correct use of articles was also explored. In addition, the difference in the students’ attitudes towards feedback type in different groups was compared. The treatments were different CF types on different functional uses of articles. Students in Group one (DCF alone) received direct error correction above each article error. Group two (DCF-WMLE) received direct error correction above each article error and written meta-linguistic explanation. Group three (DCF-OMLE) received direct error correction above each article error and oral meta-linguistic explanation. Group four (DCF-W/OMLE) received direct error correction as well as written and oral metalinguistic explanation above each article error. Group five (Control) did not receive any type of direct corrective feedback or any written or oral meta-linguistic explanation, instead the article errors were underlined. Shiraz University of Medical Sciences in Iran was chosen for the data collection. Nonequivalent control group design was, a type of quasi-experimental research design, was employed in this study because it was a suitable research design to control most of the internal and external validity threats. Data were collected based on purposive sampling from 140 (69 males and 71 females) first year Iranian EFL medical students who enrolled in General English classes. There were six treatment sessions for each type of corrective feedback. Data were collected through three rational cloze tests that had been appropriated through Flesch Reading Ease readability scale and a Likert type questionnaire with seven options (from strongly disagree to strongly agree) and 15 items. The students in all five groups took the same three rational cloze tests (Pretest,post-test, and second post-test), and performed six tasks (three picture stories and three error correction tasks) all in medical contexts, and received feedback on each piece of writing from the researcher as the teacher of the course. The results of repeated measures ANOVA showed that the time-group interaction was significant (Wilks Lambda = 0.85, F (8,268) = 2.75, P = 0.006, partial eta squared = 0.076) and there was a considerable main effect for time (Wilks Lambda = 0.59, F. (2,134) = 46.72, P = 0.000). It also revealed that the type of feedback provided had a significant effect on the correct use of articles and the students who received different types of corrective feedback significantly improved their ability in using the targeted functions of the English article system properly and that they retained this ability when they were given a new test four weeks after the treatment sessions. Post-hoc comparisons indicated that only direct corrective feedback with oral metalinguistic explanation (DCF-OMLE) and direct corrective feedback with written and oral meta-linguistic feedback (DCF-W/OMLE) were effective treatment to help students in the correct use of articles. Participants in group four who received direct corrective feedback as well as written and oral meta-linguistic explanation outperformed the other experimental and control groups and resulted in significantly greater ability in the correct use of articles. Concerning the difference in attitude towards feedback type in different groups, the results of post-hoc comparisons revealed that the students’ attitudes were not the same towards different corrective feedback. It also indicated that the students in group one (DCF alone) had neutral attitudes toward corrective feedback. The students in the second group (DCFWMLE) and the third group (DCF-OMLE) had slight positive attitudes toward corrective feedback. The students in group four (DCF-W/OMLE) had the positive attitude toward the feedback they received. The results of correlation coefficients indicated that there was a correlation between the students’ attitudes and their performance on cloze tests.